Low-End Disruptive Innovation and Market Share Growth: A Case Study of Xiaomi in the Global Smartphone Industry - Chen, Xinmei (Exploring Science Academic Conference Series, 2026)
The smartphone world has been getting more competitive, as the leading companies have traditionally been oriented towards innovation at the high end. Nevertheless, Xiaomi is disrupting this trend due to the implementation of low-end disruptive innovation. This paper discusses how the Xiaomi strategy, which involves cost-efficiency, online sales, and quick product development has led to its expansion in market share in the global smartphone market. The study uses a qualitative, theoretically informed analysis grounded on the paradigm of disruptive innovation, and how companies can initially serve underserved or price-sensitive customers and subsequently be able to grow into mainstream markets. The results indicate that Xiaomi could achieve its market penetration by offering both low prices and high perceived value, which allowed it to enter the new markets and develop over time to compete with the well-established global brands. Moreover, its online environment and community-based strategy reinforced customer interaction and decreased the operational expenses. The research paper adds to the knowledge of how emerging-market companies can adopt disruptive strategies to realise rapid global growth. It also highlights the continued relevance of disruptive innovation theory in explaining competitive dynamics in modern technology markets.